Prevention of bug bites, stings, and disease - Strickman, Daniel; Frances, Stephen P.; Debboun, Mustapha (New York ; Oxford : Oxford University Press, 2009)
This guide provides anyone, anywhere with the information they need to prevent bites and stings from scorpions, spiders, mites ticks, centipedes, lice, and other such creatures.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Arthropoda; Bites and stings